2007
DOI: 10.1016/j.physa.2006.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Re-entrant phase transitions of the Blume–Emery–Griffiths model for a simple cubic lattice on the cellular automaton

Abstract: . IntroductionThe Blume-Emery-Griffiths (BEG) model 1 was originally introduced in order to explain the phase separation and superfluidity in the He 3 -He 4 mixtures. Subsequently, the model was used in the description of a variety of different physical phenomena such as multicomponent fluids 2 , microemulsions 3 , and semiconductors alloys 4 , etc.The Hamiltonian of the BEG model is given by,where s i = ±1, 0 and < ij > denotes summation over all nearest-neighboring (nn) spin pairs on a simple cubic lattice. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 42 publications
(9 reference statements)
1
9
0
Order By: Relevance
“…In the previous papers, the Creutz and AB 3 ) type stoichiometric structures on the fcc BEG model using the heating algorithm [15,16] The CA results for the 5% heating rate nearly agree with the CVM and MFA results for the critical lines. In addition, it is seen that the fcc BEG model on the cellular automaton exhibits the modulated AB (type-II) phase as indicated by the theoretical studies [31,36,37] and the experimental results [39, 41 − 47] for Cu-Au type structures.…”
supporting
confidence: 59%
See 1 more Smart Citation
“…In the previous papers, the Creutz and AB 3 ) type stoichiometric structures on the fcc BEG model using the heating algorithm [15,16] The CA results for the 5% heating rate nearly agree with the CVM and MFA results for the critical lines. In addition, it is seen that the fcc BEG model on the cellular automaton exhibits the modulated AB (type-II) phase as indicated by the theoretical studies [31,36,37] and the experimental results [39, 41 − 47] for Cu-Au type structures.…”
supporting
confidence: 59%
“…This algorithm is realized by increasing of 5% in the kinetic energy (H k ) of each site [15]. Therefore, the increasing value per site of H k is obtained from the integer part of the 0.05H k .…”
Section: Resultsmentioning
confidence: 99%
“…The CCA algorithm is a microcanonical algorithm interpolating between the canonical Monte Carlo and molecular dynamics techniques on a cellular automaton, and it was first introduced by Creutz [14]. In the previous papers [14][15][16][17][18][19][20][21], the CCA algorithm and improved algorithms from CCA were used to study the critical behavior of the different Ising model Hamiltonians in two and three dimensions. It was shown that they have successfully produced the critical behavior of the models.…”
Section: Introductionmentioning
confidence: 99%
“…It has been analyzed using mean-field approximation (MFA) [2][3][4][5][6], renormalization techniques [7,8], cluster variation method (CVM) [9][10][11][12][13], effective field theory [14,15], Monte Carlo renormalization method (MCRG) [16], Monte Carlo simulations [17][18][19][20] and cellular automaton simulations [21][22][23]. The BEG model is described by the Hamiltonian…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in this study, our interest is focused to study the ferrimagnetic phase of the BEG model in the case of K /J < 0. Recently, we studied the re-entrant behavior of the BEG model in the case of K /J < 0, using an improved heating algorithm [21][22][23] from the Creutz cellular automaton (CCA) [24][25][26][27][28][29][30][31][32]. It was obtained that the model can show the re-entrant and double re-entrant phase transitions (PTs) for some values of the D/J and K /J parameters.…”
Section: Introductionmentioning
confidence: 99%